Analisis Penerapan Model Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Sikap Kompetitif Belajar pada Siswa Sekolah Dasar - Acil Ridwan; Euis Nur Amanah Asdiniah; Mae Afriliani (Journal on Education, 2022)
This research is qualitative research. This study aims to analyze the application of the Student Teams Achievement Division (STAD) model. The research method in this research is descriptive research. The subjects of this study were elementary school students. The collection of data obtained in this study is a literature study. The results of the research in this article show that the application of the STAD learning model is very good to be applied to increase the competitive attitude of elementary school students. The STAD model has 6 steps, namely: Delivering learning objectives and motivating students, presenting information, organizing students in groups, guiding work and study groups, evaluating, and giving awards. The impact of this learning can be seen during the learning process, namely by looking at the teacher and students who have implemented the 6 steps of the learning model correctly, so that the learning process goes well, the interaction between students and teachers or students and students also looks good, and students can interact in groups.